MODIFICATION OF THE DIFFICULTY OF FACILITIES AND INFRASTRUCTURE IN SALAF SCHOOLS WITH THE BELIEF, TRULY WITH DIFFICULTY THERE IS EASE - Zainuri, Muhammad; Topo Yono (Gladi : Jurnal Ilmu Keolahragaan, 2025)
Salaf Schools, as Islamic educational institutions, often face limited facilities and infrastructure. This study aims to analyze the obstacles and challenges in providing sports facilities and infrastructure, especially badminton, in Salaf schools that have limited facilities. Creative modifications such as the use of used bottles as a substitute for rackets are carried out to overcome these limitations. This study uses a qualitative approach with descriptive methods and case studies. Data were collected through semi-structured interviews with teachers and principals, as well as observations of sports facilities in schools. The results of the study showed that although the tools used were not standard, these modifications increased student participation and enthusiasm in sports learning. The principle of "indeed with difficulty there is ease" was applied to motivate teachers and students to remain creative and productive in facing limitations. This innovative solution succeeded in creating an interactive learning atmosphere and supporting students' physical development.